What does first-line therapy mean for paediatric multiple sclerosis in the current era?. (November 2021) - Hacohen, Yael; Banwell, Brenda; Ciccarelli, Olga
Paediatric multiple sclerosis (MS) is associated with higher relapse rate, rapid magnetic resonance imaging lesion accrual early in the disease course and worse cognitive outcome and physical disability in the long term compared to adult-onset disease. Current treatment strategies are largely centre-specific and reliant on adult protocols. The aim of this review is to examine which treatment options should be considered first line for paediatric MS and we attempt to answer the question if injectable first-line disease-modifying therapies (DMTs) are still an optimal option. To answer this question, we review the effects of early onset disease on clinical course and outcomes, with specific considerations on risks and benefits of treatments for paediatric MS. Considering the impact of disease activity on brain atrophy, cognitive impairment and development of secondary progressive MS at a younger age, we would recommend treating paediatric MS as a highly active disease, favouring the early use of highly effective DMTs rather than injectable DMTs.